The association between digitalization and mental health: The mediating role of wellbeing at work - Sun, Jianmin; Shen, Hongzhou; Ibn-ul-Hassan, Syed; Riaz, Amir; Domil, Aura Emanuela (Frontiers in Psychiatry, 2022)
The study aims to measure the mediating relationship of well-being at work between digitalization (IT infrastructure, IT business spanning, and IT proactive stance) and their effect on mental health. The study uses primary data collection techniques to gather data and used purposive sampling to analyze the data. The sample size of the study is 349 respondents. The research uses Smart PLS software to measure the relationship through bootstrapping and algorithms. The study finds a significant positive mediating role of well-being between digitalization (IT infrastructure, IT business spanning, and IT proactive stance) and their effect on mental health. The study outcomes are helpful for managers and policymakers.